2015
DOI: 10.1002/jcop.21739
|View full text |Cite
|
Sign up to set email alerts
|

Community Sense of Coherence Among Adolescents as Related to Their Involvement in Risk Behaviors

Abstract: The current study employs a new concept–community sense of coherence (CSOC)–that measures youth's perceptions of their own community and its potential as a source for protective factors and assets. The theoretical foundation for this measure is the salutogenic approach and its concept of “sense of coherence.” A total of 1023 students from the 8th to 11th grades, living in 3 Israeli communities, filled out self‐reported questionnaires that included measures of CSOC and involvement in risk behaviors. Results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 51 publications
(65 reference statements)
1
25
0
Order By: Relevance
“…Elfassi, Braun‐Lewensohn, Krumer‐Nevo, and Sagy () also found that youth with a positive neighborhood SOC were both more empowered and more likely to participate in community organizations. In this same study, the authors also highlighted that community perceptions and involvement offset involvement in drug and alcohol use (Elfassi et al., ), albeit community participation tends to have a weaker relationship with PE directly and is often indirectly associated with PE through other variables (Speer et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elfassi, Braun‐Lewensohn, Krumer‐Nevo, and Sagy () also found that youth with a positive neighborhood SOC were both more empowered and more likely to participate in community organizations. In this same study, the authors also highlighted that community perceptions and involvement offset involvement in drug and alcohol use (Elfassi et al., ), albeit community participation tends to have a weaker relationship with PE directly and is often indirectly associated with PE through other variables (Speer et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Elsewhere, studies have determined that racial and ethnic minority youth, involved in school and community activities, had more leadership qualities (Eisman et al., ; Peterson, Speer, & Peterson, ), higher grade‐point averages (Fredricks & Eccles, ), greater academic self‐esteem (Christens & Peterson, ), a desire to attend college or other institutions (Chan, ), and a lower probability of engaging in substance‐using behaviors (Elfassi et al., ). Longitudinal investigations have corroborated such results and emphasized the importance of community participation and civic action (e.g., involvement in clubs at school or talking with adults about community issues) in predicting PE (Christens et al., ), positive academic futures, and positive behavioral outcomes into emerging adulthood (Chan et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Neighborhood SOC is based in concepts of collective efficacy and neighboring (i.e., sharing neighbors and mutual assistance; Perkins & Long, ) and has been broadly defined as perceived feelings of belongingness and a shared belief that community members will meet one another's needs through these relationships (McMillan & Chavis, ). Scholars agree that neighborhood SOC not only has a positive influence on communities and individuals but also shapes how people participate within and among the collective toward broader social change (Chavis, Hogge, McMillan, & Wandersman, ; Elfassi, Braun‐Lewensohn, Krumer‐Nevo, & Sagy, ; Long & Perkins, ; Mannarini, Rochira, & Talò, ; McMillan & Chavis, ; Peterson, Speer, & McMillan, ; Sarason, ). McMillan and Chavis () defined the following four dimensions to neighborhood SOC: Membership–feeling of belongingness or relatedness to the organization or community. Influence–the feeling of making a difference in the group and mattering as a member. Needs fulfillment–the perception that members will meet one another's needs, and resources will be shared through these relationships. Emotional connection–a shared emotional connection or experience, through history or common places. …”
mentioning
confidence: 99%
“…Influence considers who individuals make decisions within and among the collective and how the influence of the larger group on one's decision making. Needs fulfillment is the perception that one's community will meet their needs, which suggests that social credentials and resources are transformed between individuals and groups to both meet needs and fulfill the needs of the broader collective (Elfassi et al., ; Nowell & Boyd, ). Last, shared emotional connection is based on those common experiences shared among individuals and the collective and how these experiences strengthen social ties among members (Mannarini et al., ).…”
mentioning
confidence: 99%
“…It constitutes the three components of SOC: comprehensibility, manageability, and meaningfulness (BraunLewensohn & Sagy, 2011;Elfassi, Braun-Lewensohn, Krumer-Nevo, & Sagy, 2016;Peled, Sagy, & BraunLewensohn, 2013;Sagy, 1998). Community comprehensibility relates to the perception that life in one's community is predictable, safe, and secure and that one's community is a place which is known and understood.…”
Section: Introductionmentioning
confidence: 99%